1970
DOI: 10.3329/jname.v3i1.925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure and Notches on the Fracture Toughness of Medium Carbon Steel

Abstract: Fracture toughness (K 1C )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 4 publications
2
21
0
4
Order By: Relevance
“…The improvement in fracture toughness with increase in BLA content may be attributed to the presence of silica, which is a softer ceramic in comparison with SiC. The results obtained are validated by the fact that the fracture toughness of most of the engineering materials varies inversely with the yield strength [48,49]. The results are in line with those obtained by Alaneme et al [26], who determined the fracture toughness values of hybrid composites by circumferential notched tensile (CNT) specimens.…”
Section: Fracture Toughnesssupporting
confidence: 86%
See 1 more Smart Citation
“…The improvement in fracture toughness with increase in BLA content may be attributed to the presence of silica, which is a softer ceramic in comparison with SiC. The results obtained are validated by the fact that the fracture toughness of most of the engineering materials varies inversely with the yield strength [48,49]. The results are in line with those obtained by Alaneme et al [26], who determined the fracture toughness values of hybrid composites by circumferential notched tensile (CNT) specimens.…”
Section: Fracture Toughnesssupporting
confidence: 86%
“…The hybrid composites containing 2 wt.% and 3 wt.% RHA contents possessed higher fracture toughness values as compared to the ceramics reinforced composite [26]. The primary mechanisms of fracture have been attributed to particle cracking, interfacial cracking or particle debonding [48]. Ceramic particulates are generally hard and brittle.…”
Section: Fracture Toughnessmentioning
confidence: 98%
“…In accordance with Nath and Das [11], the reliability of the CNT testing method and the achievement of the plane strain condition were evaluated using the relations:…”
Section: Experimentationmentioning
confidence: 99%
“…Mechanical characterization such as tensile strength and elongation experiments by using Universal Testing Machine (UTM) of Al/SiC has been reported [8] for varying mass fraction of SiCp with Aluminium. Hardness [2], Fracture toughness [3,4], tensile fracture behavior on Circumferential Notched Tensile (CNT) Specimens [5,6] on Compact Tension (CT) test specimen [13,14] of Al/SiC was studied by different researchers and most of them compared their results with the unreinforced aluminium alloy. In this research work, a new method of finding the fracture toughness, using Circumferential Notched Tensile (CNT) Specimens, is utilized which is a recent advance in fracture toughness testing method is adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture of materials depends upon many parameters like the state of stress, strain rate, the defect size, crystal structure, chemical homogeneity, grain size, grain boundary, formation of twins and slip plane, temperature and environmental conditions. In an experimental study, Nath and Das [14] found that fine grained structure have higher value of fracture toughness than a coarse grained structure for medium carbon steel. Many scientists have proposed many theories both in microscopic and macroscopic levels.…”
Section: Introductionmentioning
confidence: 99%